Marine cosmetics and the blue bioeconomy - Rotter, Ana; Varamogianni-Mamatsi, Despoina; Zvonar Pobirk, Alenka; Gosenca Matjaž, Mirjam; Cueto, Mercedes; Díaz Marrero, Ana R.; Berden Zrimec, Maja; Grigalionyte-Bembič, Ernesta; Klun, Katja; Zidar, Luen; Baebler, Špela; Lukić-Bilela, Lada (iScience, 2024)
As the global population continues to grow, so does the demand for longer, healthier lives and environmentally responsible choices. Consumers are increasingly drawn to naturally sourced products with proven health and wellbeing benefits. The marine environment presents a promising yet underexplored resource for the cosmetics industry, offering bioactive compounds with the potential for safe and biocompatible ingredients. This manuscript provides a comprehensive overview of the potential of marine organisms for cosmetics production, highlighting marine-derived compounds and their applications in skin/hair/oral-care products, cosmeceuticals and more. It also lays down critical safety considerations and addresses the methodologies for sourcing marine compounds, including harvesting, the biorefinery concept, use of systems biology for enhanced product development, and the relevant regulatory landscape. The review is enriched by three case studies: design of macroalgal skincare products in Iceland, establishment of a microalgal cosmetics spin-off in Italy, and the utilization of marine proteins for cosmeceutical applications.